(untitled) (ResearchJet Journal of Analysis and Inventions, 2021)
The article discusses the importance of teaching physics, as well as the benefits of developing creative thinking skills in children along with science, and several effective methods. Creativity is the ability to see a problem, to solve it in an unusual way, and this quality is the basis of new scientific discoveries, inventions and knowledge.